2011
DOI: 10.1002/ejoc.201100339
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenized Wilkinson‐Type Catalyst for Transfer Hydrogenation of Carbonyl Compounds

Abstract: Wilkinson's catalyst [RhCl(PPh 3 ) 3 ] was heterogenized on common silica by the use of a grafting/anchoring technique. The immobilized catalyst showed high activity and selectivity in transfer hydrogenation reactions of a range of carbonyl compounds in 2-propanol. Reactions carried out in 2-propa-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…RhCl(PPh 3 ) 3 catalytic system gave only 4% of the same product [46]. Likewise, the present system was found to be effective in the reduction of 2-furfuraldehyde which gave 74% of the product ( …”
Section: Extension Of Scopesupporting
confidence: 50%
“…RhCl(PPh 3 ) 3 catalytic system gave only 4% of the same product [46]. Likewise, the present system was found to be effective in the reduction of 2-furfuraldehyde which gave 74% of the product ( …”
Section: Extension Of Scopesupporting
confidence: 50%
“…Several groups have reported a “boron enhancement effect” in the catalytic system. ,, The complexes in this article seem to be appropriate candidates for the investigation of such an effect. Some Rh(I) and Ir(I) complexes are known to catalyze transfer hydrogenation of ketones, and it was found that the base also accelerates these reactions . Recently, Owen et al reported that an azaindoyl borane-based Rh(I) complex bearing the Rh–H–B linkage catalyzed hydrogen transfer of several ketones in strong basic conditions and that the Rh–H–B linkage appears to be a key factor in exhibiting high catalytic activity due to the cooperative activation induced by Rh and B atoms .…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that 2-acetylthiophene was transformed to 1-thiophene ethanol (90%) with high selectivity, while silicabound RhCl(PPh 3 ) 3 -catalyzed reduction gave only 4% of the product. 88 Similarly, 1-furyl ethanone yielded 1-furyl ethanol in 76% yield, whereas Pt/Al 2 O 3 -catalyzed reaction yielded only 50% of the product. 89 The results concluded that the u-GNS-RuO 2 NRs effectively reduce various ketones; this confirms that the proposed catalyst (GNS-RuNPs) is highly stable and versatile.…”
Section: Extension Of Scopementioning
confidence: 99%